Advances in Human Factors, Business Management and Leadership Proceedings of the AHFE 2017 International Conferences on Human Factors in Management and Leadership, and Business Management and Society, July 17−21, 2017, The Westin Bonaventure Hotel, Los Angeles, California, USA - Kantola, Jussi Ilari; Barath, Tibor; Nazir, Salman; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book reports on practical approaches for facilitating the process of achieving excellence in the management and leadership of organizational resources. It shows how the principles of creating shared value can be applied to ensure faster learning, training, business development, and social renewal. In particular, the book presents novel methods and tools for tackling the complexity of management and learning in both business organizations and society. It covers ontologies, intelligent management systems, methods for creating knowledge and value added. It gives novel insights into time management and operations optimization, as well as advanced methods for evaluating customers' satisfaction and conscious experience. Based on two conferences, the AHFE 2017 International Conference on Human Factors, Business Management and Society and the AHFE 2017 International Conference on Human Factors in Management and Leadership, held on July 17-21, 2017, in Los Angeles, California, USA, the book provides both researchers and professionals with new tools and inspiring ideas for achieving excellence in various business activities.
Working life within a hybrid world - how digital transformation and agile structures affect human functions and increase quality of work and business performance -- The value analysis in the investment evaluation of innovative productions -- Management style, focus and purpose in development of LEAN in university hospital -- The social responsibility in Mexico: A review of the literature -- Motivation and work: A survey of the motivational aspects in industries -- Effects of occupational health and safety assessment series (OHSAS) standard: A study on core competencies building and organizational learning -- Research on enterprise personnel safety awareness based on Voronoi Diagram.
Keywords: Computational intelligence; Personnel management; Data mining; Strategic planning; Leadership; Operations research; Computational Intelligence; Human Resource Management; Data Mining and Knowledge Discovery; Business Strategy and Leadership; Operations Research and Decision Theory